1992
DOI: 10.1007/bf01702560
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-nucleotide sequence of an ordinary strain of potato virus S

Abstract: The sequence of 1346 nucleotides of the 3'-terminal region of an ordinary strain of potato virus S was determined from cloned cDNA. This portion of the viral RNA contains two major open reading frames (ORFs), encoding the coat protein of M(r)33K and a protein of M(r)11K 3' to the coat protein, both of which showed high homology, 93% and 79%, respectively, with the equivalent proteins of the Andean strain. A major block of amino acids that differ between the ordinary and Andean strains was present in both the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…The virus forms minor amounts of two subgenomic RNAs (2.5 and 1.5 kb), which are included in the flexuous virus particles. The smaller subgenomic RNA codes for the CP and the 11-kDa protein [11]. It is proposed that this subgenomic RNA has highly active translation-enhancing leader sequence [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus forms minor amounts of two subgenomic RNAs (2.5 and 1.5 kb), which are included in the flexuous virus particles. The smaller subgenomic RNA codes for the CP and the 11-kDa protein [11]. It is proposed that this subgenomic RNA has highly active translation-enhancing leader sequence [32].…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that this subgenomic RNA has highly active translation-enhancing leader sequence [32]. On the basis of systemic and non-systemic infection in Chenopodium spp., PVS has been classified in two strains namely ordinary strain (PVS O ) and Andean strain (PVS A ) [11,14,30]. However, as suggested recently by Cox and Jones [5], the term PVS A based on molecular characterization be applied strictly to members of the genetically distinct clades and not all isolates to invade Electronic supplementary material The online version of this article (doi:10.1007/s11262-011-0619-3) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of similarity between seven carlaviruses for which sequence information has been reported is shown within the enclosed box. The sequence and distance from the start of the poly(A) tail is shown for chrysanthemum virus B [CVB; Levay and Zavriev, 1991], potato virus M [PVM; Zavriev et al, 1991], lily symptomless virus [LSV; Memelink et al, 1990], Helenium virus S [HeLVS; Foster et al, 1990], potato virus S [PVS; Foster and Mills, 1992;MacKenzie et al, 1989] [sequence in this region is identical in both ordinary and Andean strains of PVS], blueberry scorch virus [BScV; Cavileer et al, 1994] [sequence is present in 3 strains of the virus] and cowpea mild mottle virus (CMMV) (from information reported in this paper); (b) Agarose gel analysis of PCR products generated using Carla-Uni and anchored oligo-d(T) primers on first-strand cDNA generated from RNA isolated from plant material infected with a range of viruses (known carlaviruses, possible carlavimses and viruses of other genera with filamentous particles), as outlined below. Lane A, molecular weight markers (Superladder; Advanced Biotechnologies); lane B, molecular weight markers (kilobase ladder; Gibco BRL).…”
mentioning
confidence: 99%
“…Contained within this region, was a partial ORF of 19.5K and a 3 ~ terminal ORF of 11.7K, which displayed high similarity with the C-terminal region of the coat protein and the 11K ORFs of two previously sequenced carlaviruses. A comparison of the amino acid sequences of the CMMV ORFs and two carlaviruses, PVS [Foster and Mills, 1992;MacKenzie et at., 1989] and HeLVS [Foster, et al, 1990], showed that CMMV has 56% similarity with PVS and 54% with HeLVS within the coat protein at the amino acid level, and 48% with PVS and 46% with HeLVS over the 11K ORF (Figs. 2B, 2C).…”
mentioning
confidence: 99%
“…Sequence analysis of group members has revealed six major open reading frames (ORF). The 3' coding regions of several group members such as potato virus M (PVM) [18], the ordinary strain of potato virus S (PVS °) [5] and lily symptomless virus (LSV) [14] have recently been determined, revealing a triple gene block, of three ORFs of approximately 25 K, 12 K and 7 K upstream from the coat protein (CP) gene. The 3' terminal cistron encodes a protein approximately 11 K in size and it is the presence of this protein that distinguishes carlaviruses from the closely…”
mentioning
confidence: 99%